Lebensbilder - Berthelt, Friedrich A.; Jäkel, Julius; Petermann, Karl Gottlieb; Thomas, Louis (Druck und Verlag von Julius Klinkhardt, 1873)
Anhang (8 Seiten): Das Königreich Sachsen (Geographie und Geschichte)